Control-flow Refinement and Progress Invariants for Bound Analysis - Gulwani, Sumit; Jain, Sagar; Koskinen, Eric (PLDI '09 Proceedings of the 30th ACM SIGPLAN Conference on Programming Language Design and Implementation, 2009)
Symbolic complexity bounds help programmers understand the performance characteristics of their implementations. Existing work provides techniques for statically determining bounds of procedures with only simple control-flow. However, procedures with nested loops or multiple paths through a single loop are challenging. In this paper we describe two techniques, control-flow refinement and progress invariants, that together enable estimation of precise bounds for procedures with nested and multi-path loops. Control-flow refinement transforms a multi-path loop into a semantically equivalent code fragment with simpler loops by making the structure of path-interleaving explicit. We show that this enables non-disjunctive invariant generation tools to find a bound on many procedures for which previous techniques were unable to prove termination. Progress invariants characterize relationships between consecutive states that can arise at a program location. We further present an algorithm that uses progress invariants to compute precise bounds for nested loops. The utility of each of the above techniques go beyond our application to symbolic bound analysis. In particular, we discuss applications of control-flow refinement to proving safety properties that otherwise require disjunctive invariants. We also discuss applications of progress invariants to proving fair termination. We have applied our methodology to a significant commercial product and were able to find symbolic bounds for 90% of the loops. We are not aware of any other published results that report experiences running a bound analysis on a real code-base.